Manfaat Ekstrak Kunyit (Curcuma domestica Val.) Dalam Menghambat Pertumbuhan Staphylococcus aureus - Putri, Putu Winna Deyanti; Rusyati, Luh Made Mas; Praharsini, I Gusti Agung; Sudarsa, Prima Sanjiwani Saraswati (E-Jurnal Medika Udayana; Vol 12 No 3 (2023): E-Jurnal Medika Udayana, 2023)
Background : Staphylococcus aureus is an major human pathogen. Most individuals get Staphylococcus aureus infections with varying degrees of malignancy, such as superficial pyoderma, at some point in their lives. Antibiotics are often used to treat Staphylococcus aureus infections, however they may not be utilised or prescribed correctly, resulting in resistance. Alkaloids, flavonoids, tannins, essential oils, terpenoids, and curcuminoids are some of the active components in turmeric that have antibacterial properties. Objective: The goal of this study was to see how efficient the most effective turmeric extract (Curcuma domestica Val.) was in stopping Staphylococcus aureus from growing. Methods: This is an experimental research with a post-test control group. A maceration process employing 96 percent ethanol as a solvent was used to extract Singaraja turmeric. The extract concentrations employed in this research were 15%, 30%, 50%, 75%, and 100%; the positive control was vancomycin, and the negative control was 96 percent ethanol. Using the disc spreading approach, the test was conducted four times. The Kruskal-Wallis test was used to examine the findings of the research. Results: For the average, the inhibition zones were 7 mm, 7.25 mm, 7.5 mm, 7 mm, and 7 mm in diameter at each concentration. This research obtained significance figure by 0.001 (p<0.05). This suggests that the development of Staphylococcus aureus is influenced by varying amounts of turmeric ethanol extract. Conclusions: Turmeric extract (Curcuma domestica Val.) inhibits the growth of Staphylococcus aureus at all concentrations, with 50% of the extracts displaying the largest inhibition zone width.